Effect of Some Months on Follicles and Oocytes Recovered from Iraqi Ewes - A. Munther; T. Mohammed; A. Majeed (مجلة الانبار للعلوم البيطرية, 2021)
The aim of the current study was to know the effect of season on the numbers of follicles and Oocytes recovered during Several months. 304 genital systems of Ewes were collected from Al-Fallujah abattoir/ Al-Fallujah, Al-Anbar province, during the period from 3, January 2021 to 1, July 2021. The samples were transported with Cool Box contained normal saline to the Reproductive Biotechnology Lab/Dept. of Surgery and Obstetrics / College of Vet. Medicine, University of Fallujah. The results showed that the total numbers of Oocytes with Cumulus cells recovered were 1037 oocytes. The results also showed a significant difference (P≤ 0.01) in the numbers of follicles between the right and the left ovaries. The numbers of follicles present at right ovaries were 776 in a percentage of (56.73%) from the total numbers where it was 592 follicles at the left ovaries in a percent of (43.27%) from the total numbers. It has been observed superiority of right ovary on the left ovary in the numbers of oocytes recovered, where it was 603 oocytes (58.15 %) from the right ovary and 434 oocytes (41.85 %) from the Left ovary. Also, the results showed a high Significant difference (P≤ 0.01) in the size of large and small follicles numbers. when the small follicles have large numbers. It has been also concluded from this study that there was a significant difference (P≤ 0.01) in the numbers of follicles and oocytes between the months of March and April as compared with other months.